Optimalisasi Hukum terhadap Pemenuhan Hak - Hak Pekerja Penyandang Disabilitas atas Akses dan Fasilitas Pendukung di Kabupaten Indramayu - Dirkareshza, Rianda; Sadiawati, Diani; Prawira, M. Rizki Yudha; Aryaputri, Aqila Shafiqa; Falevi, Yunizar (Jurnal Ilmiah Penegakan Hukum, 2023)
Every Indonesian citizen has the right to get a decent job, as mandated in Article 27 of the 1945 Constitution. The right to get a job belongs to every Indonesian citizen, including citizens with disabilities. However, discrimination and difficulties often occur in accessing the supporting facilities needed by workers with disabilities. This research aims to socialize the quality of implementation of law enforcement towards fulfilling the rights of workers with disabilities regarding access and supporting facilities in the workplace, and how the optimization of the law can improve the fulfillment of the rights of workers with disabilities regarding access and supporting facilities in the workplace, especially in Indramayu Regency area. This research uses a normative method complemented by interviews with a statutory and conceptual approach and uses descriptive and qualitative analysis techniques. The results of the research show that: First, the Indramayu Regency Government has not met the 2% requirement for employing people with disabilities in the government sector by Law Number 8 of 2016 concerning People with Disabilities. Second, based on literature studies and comparisons of regional regulations in the last 3 years, there have been many regulations that specifically regulate the empowerment and protection of people with disabilities to get decent work, so it would be best for the Indramayu Regency Government to immediately prepare and ratify related Regional Regulations regarding the empowerment and protection of people with disabilities.